Kinetochore Biorientation in Saccharomyces cerevisiae Requires a Tightly Folded Conformation of the Ndc80 Complex. Issue 4 (16th September 2014) - Tien, Jerry F; Umbreit, Neil T; Zelter, Alex; Riffle, Michael; Hoopmann, Michael R; Johnson, Richard S; Fonslow, Bryan R; Yates, John R; MacCoss, Michael J; Moritz, Robert L; Asbury, Charles L; Davis, Trisha N
Abstract: Accurate transmission of genetic material relies on the coupling of chromosomes to spindle microtubules by kinetochores. These linkages are regulated by the conserved Aurora B/Ipl1 kinase to ensure that sister chromatids are properly attached to spindle microtubules. Kinetochore–microtubule attachments require the essential Ndc80 complex, which contains two globular ends linked by large coiled-coil domains. In this study, we isolated a novel ndc80 mutant in Saccharomyces cerevisiae that contains mutations in the coiled-coil domain. This ndc80 mutant accumulates erroneous kinetochore–microtubule attachments, resulting in misalignment of kinetochores on the mitotic spindle. Genetic analyses with suppressors of the ndc80 mutant and in vitro cross-linking experiments suggest that the kinetochore misalignment in vivo stems from a defect in the ability of the Ndc80 complex to stably fold at a hinge in the coiled coil. Previous studies proposed that the Ndc80 complex can exist in multiple conformations: elongated during metaphase and bent during anaphase. However, the distinct functions of individual conformations in vivo are unknown. Here, our analysis revealed a tightly folded conformation of the Ndc80 complex that is likely required early in mitosis. This conformation is mediated by a direct, intracomplex interaction and involves a greater degree of folding than the bent form of the complex at anaphase. Furthermore, our results suggest that this conformation is functionally important in vivo for efficient error correction by Aurora B/Ipl1 and, consequently, to ensure proper kinetochore alignment early in mitosis.